IMPLEMENTASI INCREMENTAL METHOD PADA RANCANG BANGUN WEBSITE PENERBIT PNP PRESS - Ikhbal Salam, Riyan; Ikhsan; Rayendra; Ismael; Eka Putra, Dian; Ramadhani (ITP Press, 2025)
PNP Press publisher is one of the publishers in Indonesia which is under the auspices of the Padang State Polytechnic State University. This publisher publishes two publishing models, namely magazines and books. The types of books published at PNP Press are scientific books, texts, and references. Meanwhile, the types of articles published in magazines are popular articles and articles from several columns. With the increasing demand for book and magazine publications at this publisher, a system is needed that can manage the publication process effectively and efficiently. This research aims to design and implement a website that can facilitate the publication and distribution process of magazines and books at PNP Press using the Incremental method. This method was chosen because it can accommodate various needs during the system development process. Using the Incremental Method in building publisher websites has proven capable of producing PNP Press publisher websites that suit user needs and ensure the system can be implemented effectively, namely in the form of books published using the open monograph press (OMP) and magazines using the open journal system (OJS).